European Congress of Mathematics 2018
DOI: 10.4171/176-1/38
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on Bernoulli convolutions

Abstract: The Bernoulli convolution with parameter λ ∈ (0, 1) is the measure on R that is the distribution of the random power series ±λ n , where ± are independent fair coin-tosses. This paper surveys recent progress on our understanding of the regularity properties of these measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 55 publications
0
27
0
1
Order By: Relevance
“…with σ i = 0 and σ i σ j = δ i,j . From the previous equation, we see that the distribution of the variable x n is determined by the distribution of the random variable Θ n = n−1 j=0w n σ n , withw = 1 − w. In the mathematical community, the distribution of Θ is known as Bernoulli convolutions [32,33,34,35,36,37,38,39]. In 1935 Jessen and Wintner [33] proved that for 0 <w < 1 the distribution of Θ is either absolutely continuous or singular with respect to Lebesgue measure.…”
Section: The Average Number Of Fermions In the System: N Nmentioning
confidence: 99%
See 1 more Smart Citation
“…with σ i = 0 and σ i σ j = δ i,j . From the previous equation, we see that the distribution of the variable x n is determined by the distribution of the random variable Θ n = n−1 j=0w n σ n , withw = 1 − w. In the mathematical community, the distribution of Θ is known as Bernoulli convolutions [32,33,34,35,36,37,38,39]. In 1935 Jessen and Wintner [33] proved that for 0 <w < 1 the distribution of Θ is either absolutely continuous or singular with respect to Lebesgue measure.…”
Section: The Average Number Of Fermions In the System: N Nmentioning
confidence: 99%
“…Since then the challenge has been to identify the set ofw values for which the distribution is absolutely continuous or singular. Amongst the many noticeable results (see reviews [34,35]), P. Erdos [36] showed that the density is singular for allw ∈]1/2, 1[ such that 1/w is a Pisot number. No other than reciprocal Pisot numbers are known to be associated to a singular distribution [35].…”
Section: The Average Number Of Fermions In the System: N Nmentioning
confidence: 99%
“…These are particularly interesting being the only known singular Bernoulli convolutions, see [3,19,21]. There is a long history of studying the dimensionality properties of these measures, c.f., [17,22,23] and the many references cited therein for historical information. In [6,7], Feng conducted a study of mainly unbiased Bernoulli convolutions with contraction factor the inverse of a simple Pisot number and proved that for this class of measures the set of local dimensions is an interval.…”
Section: Introductionmentioning
confidence: 99%
“…These have been extensively studied since the 1930's when Erdös [7] showed that if ̺ ∈ (1, 2) was a Pisot number, then the Bernoulli convolution was purely singular and later, in [8], that the Bernoulli convolutions were absolutely continuous for almost all ̺ ∈ (1,2). For more on the history of these classical problems see [19,21].…”
Section: Introductionmentioning
confidence: 99%